Heterozygous frameshift variants in HNRNPA2B1 cause early-onset oculopharyngeal muscular dystrophy - Hong Joo Kim; Payam Mohassel; Sandra Donkervoort; Lin Guo; Kevin O’Donovan; Maura Coughlin; Xaviere Lornage; Nicola Foulds; Simon R. Hammans; A. Reghan Foley; Charlotte M. Fare; Alice F. Ford; et al. (Nature Communications, 2022)
Missense variants in RNA-binding proteins underlie many diseases. Here the authors report an oculopharyngeal muscular dystrophy caused by heterozygous frameshift mutations in HNRNPA2B1 that alter its nucleocytoplasmic transport dynamics and result in cytoplasmic accumulation of hnRNPA2 protein.